Book Review - Manaster, Kenneth A. (Columbia Journal of Environmental Law, 2019)
CLEANING UP AMERICA: AN INSIDER’S VIEW OF THE ENVI- RONMENTAL PROTECTION AGENCY. By John Quarles. New York: Houghton Mifflin Co. 1976. Pp. xvi, 256. 8.95.